Adolescents' perceptions of the effectiveness of Vedic learning through digital platforms - Nandini, Mutiara (Dharmakirti : International Journal of Religion, Mind and Science, 2025)
Introduction: The implementation of Vedic learning through digital platforms represents an innovative approach in Hindu religious education, leveraging technological advancements to enhance learning quality and effectively impart Vedic teachings to younger generations. In an era marked by rapid technological development, the study of Hinduism, particularly Vedic teachings, must be adapted to remain relevant and engaging for adolescents. This study aims to explore Hindu adolescents' perceptions of the effectiveness of Vedic learning through digital platforms and identify the factors influencing their views on this learning method. Methods: A quantitative approach with a survey research design was employed. The sample consisted of 36 Hindu students from seventh grade, selected using proportional random sampling. Data collection was conducted through a Likert-scale questionnaire designed to assess adolescents' perceptions of ease of use, material quality, and interaction in digital learning. The collected data were analyzed using descriptive statistics to illustrate adolescents' perceptions of the effectiveness of digital Vedic learning. Findings: The findings indicate that the majority of Hindu adolescents hold a positive perception of digital Vedic learning. Key factors supporting its effectiveness include easy access to materials, flexible study schedules, and enhanced comprehension of Vedic teachings through digital visualization. However, challenges were also identified, particularly the limited direct interaction with instructors, which affects the depth of understanding of more complex Vedic concepts. Some students also expressed that they felt a lack of spiritual experience, which is typically more profound in face-to-face learning settings. Conclusion: In conclusion, digital Vedic learning is considered effective, though several challenges must be addressed, such as enhancing student-teacher interaction and ensuring the continued quality of instructional materials. Novelty/Originality of this article: With the appropriate digital platforms, Vedic education can be well received by Hindu youth and serve as a crucial tool in preserving and promoting Vedic teachings in the digital age.